1974
DOI: 10.1113/jphysiol.1974.sp010556
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the directly observed responses of mesenteric vessels of the rat to nerve stimulation and noradrenaline with the distribution of adrenergic nerves

Abstract: SUMMARY1. The effects of nerve stimulation and of the topical application of noradrenaline on arteries, capillaries and veins of the mesentery of the anaesthetized rat were examined by direct observation under a microscope. The distribution of adrenergic nerves to the vessels of the mesentery was studied using the fluorescence histochemical method.2. Principal arteries, small arteries and terminal arterioles were all innervated by a network of adrenergic fibres and they all constricted in response to the stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
89
0

Year Published

1980
1980
1994
1994

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(99 citation statements)
references
References 12 publications
10
89
0
Order By: Relevance
“…This was an unexpected finding since previous studies in the literature indicated that, in general, venules receive little or no innervation. Anatomical studies of rat mesenteric venules (Furness, 1973) indicate that very few, if any, adrenergic fibres approach the venules and perivascular nerve stimulation of the same venules in vivo produced no detectable motor activity although 'reductions in the rate of flow' were observed in these vessels (Furness & Marshall, 1974). Results ofnerve stimulation in vivo are difficult to interpret and may be modified by transmitted pressures, basal neural input, hormones and local modulators, and the anaesthetic state of the animal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was an unexpected finding since previous studies in the literature indicated that, in general, venules receive little or no innervation. Anatomical studies of rat mesenteric venules (Furness, 1973) indicate that very few, if any, adrenergic fibres approach the venules and perivascular nerve stimulation of the same venules in vivo produced no detectable motor activity although 'reductions in the rate of flow' were observed in these vessels (Furness & Marshall, 1974). Results ofnerve stimulation in vivo are difficult to interpret and may be modified by transmitted pressures, basal neural input, hormones and local modulators, and the anaesthetic state of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Hirst (1977) has reported that * Present address: Harvard Medical School, Cardiovascular Division, Beth Israel Hospital,330 sympathetic nerve stimulation initiated excitatory junction potentials (e.j.p.s) in intestinal submucosal arterioles. However, no such electrical membrane response of venular smooth muscle cells to nerve stimulation has been reported and an absence of a mechanical response to nerve stimulation has been reported for mesenteric (Furness & Marshall, 1974) and intestinal submucosal venules (Hirst, 1977). Anatomical studies have, in general, shown venules to be sparsely innervated, or not innervated at all (Furness, 1971(Furness, , 1973Marshall, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…It seems likely that this difference is due to geometrical characteristics of adrenergic nerves in the mesenteric vein. Histochemical studies showed that adrenergic nerves in the mesenteric vein of rabbit and rat are sparse and are found only in the adventitial region, while there is a dense innervation in the adventitial and medial regions in arteries (Bevan et al 1974a;Furness & Marshall, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Histochemical studies of vascular smooth muscle showed that adrenergic nerves are distributed in adventitial and medial regions in the artery (Bevan, Hosmer, Ljung, Pegram & Su, 1974 a;Furness & Marshall, 1974), while in the vein, Bevan et al (1974a) found regional differences in the pattern of innervation, and that the mesenteric vein was innervated only in the adventitial regions. These adrenergic nerves contain noradrenaline which is released from the nerve as the transmitter (Bevan & Su, 1973).…”
mentioning
confidence: 99%
“…The rat mesenteric arterial bed has been shown to have dense adrenergic (Furness & Marshall, 1974), peptidergic (Ganz et al, 1986) and capsaicin-sensitive sensory (Wharton et al, 1986;Manzini & Perretti, 1988) innervation. It is conceivable that the release of NO from any of these neuronal sources may contribute to the potentiating effects of L-NAME on KCl vasoconstriction.…”
Section: Discussionmentioning
confidence: 99%